Stent‐assisted coil embolization for the treatment of aneurysm involving a coronary bifurcation. Issue 7 (12th January 2016) - Fede, Alfredo; Reimers, Bernhard; Saccà, Salvatore
Abstract : Coronary artery aneurysm (CAA) is an uncommon disease with high risks of complications including rupture and ischemia from embolic events or thrombosis, especially if associated with critical stenosis of the coronary artery. No consensus document or guidelines has been established regarding the optimal therapy for concomitant CAAs and acute coronary syndrome (ACS). Percutaneous catheter‐based treatments using only membrane‐covered stents have been described; however, only few reports of drug‐eluting stent (DES) and coil embolization for CAAs during ACS have been published to date. Therefore, we report a case of coronary artery disease with aneurysm and critical stenosis successfully treated with DES and coil embolization. © 2016 Wiley Periodicals, Inc.